2014
DOI: 10.1097/tp.0b013e3182a949fa
|View full text |Cite
|
Sign up to set email alerts
|

Brain Death–Induced Inflammatory Activity in Human Pancreatic Tissue

Abstract: Brain death induces inflammation evidenced by the up-regulation of TNF in serum and pancreatic tissue. Blocking the expression of key inflammatory mediators in brain-dead donors should be evaluated as a new approach to improve the outcomes of islet transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 49 publications
1
29
1
Order By: Relevance
“…Indeed, combining the deleterious effects of BD and IRI, microcirculation assessed by IVFM was dramatically impaired when organs from BD donors were transplanted and reperfused for 2 h as compared to naïve or sham control animals (Figure 2B and C). Contrary to already published data 27, we detected an influence of donor BD itself as compared only with naïve animals (Group III vs. Group I, p < 0.05) but not sham controls (Figure 2B).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Indeed, combining the deleterious effects of BD and IRI, microcirculation assessed by IVFM was dramatically impaired when organs from BD donors were transplanted and reperfused for 2 h as compared to naïve or sham control animals (Figure 2B and C). Contrary to already published data 27, we detected an influence of donor BD itself as compared only with naïve animals (Group III vs. Group I, p < 0.05) but not sham controls (Figure 2B).…”
Section: Discussioncontrasting
confidence: 99%
“…While it has been well described that BD causes severe alterations in donor organs, data on the impact of donor BD on pancreatic allograft quality remain scarce 26, 27. Meanwhile, one decade ago, only two experimental studies demonstrated that BD results in pathophysiological alterations in the pancreas, reflected by microcirculatory deterioration, elevated inflammatory tissue response and histological pancreas damage reducing islet yields and functionality 28, 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by our research group found that, in the case of BD donors, the pancreas appears to be damaged long before isolation, as evidenced by an increase in TNF levels in the organ (57). Another recent study has also found that the organs of BD donors produce islets of lower quality when compared to those whose donors died of heart-related causes (51).…”
Section: Islet Transplantation and The Current Status Of This Procedumentioning
confidence: 92%
“…In light of these facts, a number of islet transplantation centers have focused on the development of different methods for islet isolation and, when possible, for the selection of organs that might be more adequate for transplantation and are more likely to produce positive results in terms of the quantity and quality of isolated islets and insulin independence in the long term (37,57,60).…”
Section: Islet Transplantation and The Current Status Of This Procedumentioning
confidence: 99%